Workspace Analysis of a 2PRS/2PUS 4-DOF Parallel Mechanism - Pu Zhixin; Jin Lei (Jixie chuandong)
A new type of 2 PRS/2 PUS parallel mechanism is used to calculate the degree of freedom,and the output characteristics of the mechanism are analyzed. The inverse kinematics equation of the mechanism is established by combining the numerical algorithm with the Euler angle algorithm. In addition,the constraint conditions of the components are analyzed in detail,and the working space is solved by the comparison search method with the help of MATLAB software,moreover,the working space of the mechanism is analyzed. The research shows that the working space of the mechanism has the advantages of symmetry,no cavity and section shape regulation. The analysis results provide a theoretical basis for further research on this kind of parallel mechanism with a few degrees of freedom.